2003
DOI: 10.1097/01.iop.0000056145.71641.f5
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Orbital Decompression Combined With Fat Removal in Graves Ophthalmopathy

Abstract: Balanced medial and lateral wall decompression combined with orbital fat removal provides an effective reduction in proptosis and reduces the incidence of postoperative permanent diplopia when compared with 3-wall decompression. This technique may eliminate the need for orbital floor excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 21 publications
3
71
1
8
Order By: Relevance
“…18 Recalculation of data from studies on anterior approach three-wall orbital decompression, including translid, transconjunctival ('swinging eyelid'), and coronal techniques show relatively low NOD frequencies of 0 to 33% (Table 6). Although it was speculated that a 'balancing effect' of lateral and medial wall decompression may limit the frequency of NOD, 7,24,26,31,35,38 recent studies 25,30 failed to show a difference between translid or transconjunctival two-wall decompression and coronal three-wall decompression in that respect.…”
Section: Eyementioning
confidence: 99%
See 2 more Smart Citations
“…18 Recalculation of data from studies on anterior approach three-wall orbital decompression, including translid, transconjunctival ('swinging eyelid'), and coronal techniques show relatively low NOD frequencies of 0 to 33% (Table 6). Although it was speculated that a 'balancing effect' of lateral and medial wall decompression may limit the frequency of NOD, 7,24,26,31,35,38 recent studies 25,30 failed to show a difference between translid or transconjunctival two-wall decompression and coronal three-wall decompression in that respect.…”
Section: Eyementioning
confidence: 99%
“…1 Transantral as well as transnasal orbital decompression have been reported to induce diplopia in up to 73% of patients. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] After translid, transconjunctival, transcaruncular, [21][22][23][24][25][26][27][28][29][30] and coronal orbital decompression, 25,[30][31][32][33] as well as after combinations of these techniques, [34][35][36][37][38][39][40] diplopia was observed less frequently, while orbital fat removal seems to carry the lowest risk of inducing diplopia. [41][42] Recently, we reported on a modified 'swinging eyelid' approach for two-or three-wall orbital decompression in 19 patients with GO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After extensive lateral wall resection, Goldberg et al (2000) found an average of 5.9 mm reduction in exophthalmos, which offers a reduction of 0-0.5 mm in proptosis for each cubic millimeter of orbital volume expansion because of its location (Gonzalez et al, 2002). It has also been reported that removal of up to 25 mm of the lateral wall of the orbital rim yields only 2-2.9 cc of volume (Hitotsumatsu and Rhoton, 2000;Unal et al, 2003;Beden et al, 2007). Baldeschi et al (2005) stated that removal of the lateral wall reduces exophthalmos by 2.3 mm, with a 13% incidence of new-onset diplopia, which usually resolves spontaneously in 4-6 months.…”
Section: Discussionmentioning
confidence: 94%
“…9,14,15 Existe grande dificuldade em avaliar a presença de rinossinusite aguda após a cirurgia, pois os sintomas podem se confundir com os sintomas próprios do trauma causado pela cirurgia. Os exames de imagem em uma fase aguda tem pouca utilidade, uma vez que a presença de sangue e o edema prejudicam a avaliação.…”
unclassified